2009
DOI: 10.1007/s11738-009-0399-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of two species of inorganic arsenic on the nutrient physiology of rice seedlings

Abstract: This paper reports on a hydroponics experiment that was conducted to investigate the effect of inorganic arsenics on the seedlings of the rice cultivar Shanyou63. The seedlings were subjected to two treatments, i.e., As(III) and As(V). The results showed that the morphological traits of the seedlings were significantly altered after the arsenic treatments. Analysis of nitrogen, phosphorus, potassium, and arsenic contents of the roots and leaves of the seedlings indicated that the absorption of phosphorus and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 19 publications
(19 reference statements)
1
14
0
1
Order By: Relevance
“…In this study, we observed down regulation of AMT1 in shoots and roots at 7 d under As (III) stress. The down regulation of AMT1 was also reported in rice, lotus and mustard during As, drought and cold stress 25 , 46 , 50 . Further, at 15 d we observed upregulation of AMT1 in root under As (III) stress, again the enhanced expression of AMT1 during As (III) stress was not positively correlated with N content in plant root.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…In this study, we observed down regulation of AMT1 in shoots and roots at 7 d under As (III) stress. The down regulation of AMT1 was also reported in rice, lotus and mustard during As, drought and cold stress 25 , 46 , 50 . Further, at 15 d we observed upregulation of AMT1 in root under As (III) stress, again the enhanced expression of AMT1 during As (III) stress was not positively correlated with N content in plant root.…”
Section: Discussionmentioning
confidence: 60%
“…The ammonium reduced from nitrite subsequently assimilated into glutamine and then glutamate by glutamine synthetase (GS) and glutamate synthetase (GAGOT). Abiotic stress such as salt, drought, extreme cold and heavy metal leads to the down regulation of NRT2 and affects N uptake and assimilation in mustard and rice 25 , 46 . In the present study, result revealed downregulation of NRT2 gene in roots at 7 d, while upregulation was observed in roots at 15 d during As (III) stress, compared to control.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although studies on rice abiotic stress responses have been extensively carried out (Gao et al ), there are very few focusing on the arsenic response. In the last decade, numerous morphological, physiological and biochemical analyses have been conducted to investigate the responsive behavior of rice to arsenic (Marin et al ; Abedin and Meharg ; Ahsan et al ; Azad et al ; Shri et al ; Wang et al ). Excess arsenic can cause oxidative stress (Ahsan et al ; Shri et al ), which may inhibit seed germination (Abedin and Meharg ; Shri et al ), interfere with photosynthesis (Marin et al ), suppress growth, and eventually reduce grain yield in rice (Azad et al ; Wang et al ).…”
Section: Introductionmentioning
confidence: 99%
“…In the last decade, numerous morphological, physiological and biochemical analyses have been conducted to investigate the responsive behavior of rice to arsenic (Marin et al ; Abedin and Meharg ; Ahsan et al ; Azad et al ; Shri et al ; Wang et al ). Excess arsenic can cause oxidative stress (Ahsan et al ; Shri et al ), which may inhibit seed germination (Abedin and Meharg ; Shri et al ), interfere with photosynthesis (Marin et al ), suppress growth, and eventually reduce grain yield in rice (Azad et al ; Wang et al ). The mechanisms of arsenic uptake, translocation, extrusion, distribution and compartmentalization in rice have also been studied (Abedin et al ; Meharg and Jardine ; Ali et al ; Duan et al ; Williams et al ; Xu et al ; Zhao et al ).…”
Section: Introductionmentioning
confidence: 99%